Arthroscopic Treatment of Rotator Cuff Rupture in Patients Under 55 years Old versus Patients Older than 65 Years Old - Storti, Thiago Medeiros; Pontes Júnior, Antônio Carlos; Simionatto, João Eduardo; Simionatto, Carolina; Faria, Rafael Salomon Silva; Paniago, Alexandre Firmino (Revista Brasileira de Ortopedia, 2022)
Objective To evaluate patients submitted to arthroscopic repair of the rotator cuff (RC) comparing the results of muscle, functional strength, and pain obtained in 2 distinct groups: patients < 55 years old (G55) and patients > 65 years old (G65).Methods Data collection was performed with 63 participants (29 < 55 years old and 34 > 65 years old), in 2 moments, analyzing: A) demographic, surgical and RC lesion characteristics; B) functional variables, muscle strength, and pain.Results Higher levels of anterior elevation force, lateral, and medial rotation of the operated shoulder were observed in group G55. However, when the difference between these forces of the operated shoulder and of the contralateral shoulder was evaluated, there was no significant difference between the groups. The other variables of function and pain were similar (p > 0.05). There was also no difference between the groups in the University of California at Los Angeles Shoulder Rating Scale (UCLA) (p = 0.56) and Constant-Murley Score (p = 0.99) scores.Conclusion Arthroscopic repair of the RC in older, active, selected patients may achieve functional improvement and quality of life similar to that performed in younger patients.
Keywords: rotator cuff break; aged; arthroscopy; pain measurement; muscle strength